Complement activation and increased anaphylatoxin receptor expression are associated with cortical grey matter lesions and the compartmentalised inflammatory response of multiple sclerosis - Evans, Rhian; Watkins, Lewis M.; Hawkins, Kristen; Santiago, Gabriella; Demetriou, Constantinos; Naughton, Michelle; Dittmer, Marie; Rees, Mark I.; Fitzgerald, Denise; Morgan, B. Paul; Neal, James W.; Howell, Owain W. (Frontiers in Cellular Neuroscience, 2023)
Background: The extent of cortical pathology is an important determinant of multiple sclerosis (MS) severity. Cortical demyelination and neurodegeneration are related to inflammation of the overlying leptomeninges, a more inflammatory CSF milieu and with parenchymal microglia and astroglia activation. These are all components of the compartmentalised inflammatory response. Compartmentalised inflammation is a feature of progressive MS, which is not targeted by disease modifying therapies. Complement is differentially expressed in the MS CSF and complement, and complement receptors, are associated with demyelination and neurodegeneration. Methods: To better understand if complement activation in the leptomeninges is associated with underlying cortical demyelination, inflammation, and microglial activation, we performed a neuropathological study of progressive MS (n=22, 14 females), neuroinflammatory (n=8) and non-neurological disease controls (n=10). We then quantified the relative extent of demyelination, connective tissue inflammation, complement and complement receptor positive microglia/ macrophages. Results: Complement was elevated at the leptomeninges, subpia, and within and around vessels of the cortical grey matter. The extent of complement C1q immunoreactivity correlated with connective tissue infiltrates, whilst activation products C4d, Bb and C3b associated with grey matter demyelination, and C3a receptor 1+ and C5a receptor 1+ microglia/ macrophages closely apposed C3b labelled cells. The density of C3a receptor 1+ and C5a receptor 1+ cells was increased at the expanding edge of subpial and leukocortical lesions. C5a receptor 1+ cells expressed TNFα, iNOS and contained puncta immunoreactive for proteolipid protein, neurofilament and synaptophysin, suggesting their involvement in grey matter lesion expansion. Interpretation: The presence of products of complement activation at the brain surfaces, their association with the extent of underlying pathology and increased complement anaphylatoxin receptor positive microglia / macrophages at expanding cortical grey matter lesions, could represent a target to modify compartmentalised inflammation and cortical demyelination.